The efficacy and tolerability of glecaprevir/pibrentasvir treatment in a real-world chronic hepatitis C patients cohort - GÜNDÜZ, FEYZA (My University, 2023)
Background and Aim: The aims of the present study were to evaluate the real-life efficacy and tolerability of glecaprevir (GLE)/pibrentasvir (PIB) in the treatment of patients with chronic hepatitis C (CHC). Materials and Methods: Between May 2019 and May 2022, 686 patients with CHC, treated with GLE/PIB combination from 21 participating centers in Turkiye, were enrolled in the study. Results: All patients were Caucasian, and their median age was 56 years. At the start of GLE/PIB treatment, the median serum Hepatitis C virus RNA and serum alanine amino transaminase (ALT) levels were 6.74 log10 IU/mL and 47 U/L, respectively. Fifty-three percent of the patients were infected with genotype 1b, followed by genotype 3 (17%). Diabetes was the more common concomitant disease. The sustained virological response (SVR12) was 91.4% with intent-to-treat analysis and 98.5% with per protocol analysis. The SVR12 rates were statistically significant differences between the patients who were i.v. drug users and non-user (88.0% vs. 98.8%, p=0.025). From the baseline to SVR12, the serum ALT levels and Model for End-Stage Liver Disease score were significantly improved (p<0.001 and p=0.014, respectively). No severe adverse effect was observed. Conclusion: GLE/PIB is an effective and tolerable treatment in patients with CHC.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GASTROENTEROLOJİ VE HEPATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; GASTROENTEROLOGY & HEPATOLOGY; Gastroenteroloji; Hepatoloji; Gastroenterology; Hepatology; Chronic hepatitis C; glecaprevir-pibrentasvir; real-life experience